Reliability and responsiveness of the Jebsen‐Taylor Test of Hand Function and the Box and Block Test for children with cerebral palsy. (14th February 2019) - Araneda, Rodrigo; Ebner‐Karestinos, Daniela; Paradis, Julie; Saussez, Geoffroy; Friel, Kathleen M; Gordon, Andrew M; Bleyenheuft, Yannick
Abstract : Aim: To assess the reliability and to evaluate the responsiveness of both the Jebsen‐Taylor Test of Hand Function (JTTHF) and the Box and Block Test (BBT) in children with cerebral palsy (CP). Method: In this retrospective study, the reliability analyses were conducted with paired t ‐tests considering a short (mean 14d) and a long (mean 120d) time in between two assessment periods. In addition, an intraclass correlation coefficient (ICC) was used to assess the level of congruency. The responsiveness to therapy was conducted with a paired t ‐test in the whole sample regarding the age, the manual ability level as classified with the Manual Ability Classification System (MACS), and the topography. Results: Our main results confirmed the tests' reliability in a short time period for the JTTHF in both hands and for the BBT on the less affected hand. These results were consistent with the ICC. The responsiveness was confirmed, except on the less affected hand for the JTTHF, with similar results for age, MACS, and topography approach. Interpretation: This study supports the use of the JTTHF and the BBT to examine changes after short‐term interventions for children with CP. These results should be interpreted with association to normative values or with a control group when used over long assessment periods. What this paper adds: The Box and Block Test (BBT) is reliable in a brief period of assessment in children with cerebral palsy (CP). The Jebsen‐Taylor Test of Hand Function (JTTHF) is reliable in a brief period of assessment in children with CP. The JTTHF and BBT are responsive to changes in a brief period of intensive therapy in children with CP. The reliability and responsiveness of the JTTHF and BBT are weak over long assessment periods. What this paper adds: The Box and Block Test (BBT) is reliable in a brief period of assessment in children with cerebral palsy (CP). The Jebsen‐Taylor Test of Hand Function (JTTHF) is reliable in a brief period of assessment in children with CP. The JTTHF and BBT are responsive to changes in a brief period of intensive therapy in children with CP. The reliability and responsiveness of the JTTHF and BBT are weak over long assessment periods. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Resumen: Confiabilidad y sensibilidad de la prueba Jebsen‐Taylor Test of Hand Functión y la prueba Box and Block Test en niños con parálisis cerebral: Objetivo: Evaluar la confiabilidad y la sensibilidad de las pruebas Jebsen‐Taylor Test of Hand Function (JTTHF) y Box and Block Test (BBT) en niños con parálisis cerebral (PC). Método: En este estudio retrospectivo, los análisis de confiabilidad fueron realizados con pruebas t para muestras relacionadas, considerando un tiempo corto (media de 14 días) y largo (media de 120 días) entre dos períodos de evaluación. Además, se utilizó el coeficiente de correlación intraclase (CCI) para evaluar el grado de congruencia. La sensibilidad de la terapia fue evaluada con prueba t en toda la muestra, respecto a la edad, nivel de habilidad manual, según el sistema de clasificación de la habilidad manual (MACS), y la topografía. Resultados: Nuestros principales resultados confirman la confiabilidad a corto plazo para la prueba JTTHF en ambas manos y para la prueba BBT en la mano menos afectada. Estos resultados fueron consistentes, de acuerdo con el CCI. La sensibilidad fue confirmada, excepto en la mano menos afectada para la prueba JTTHF, con resultados similares respecto a la edad, MACS y topografía. Interpretación: Este estudio sustenta el uso de las pruebas JTTFH y BBT para evaluar cambios luego de intervenciones de corto plazo para niños con PC. Estos resultados debieran ser interpretados en asociación a valores de normalidad o con un grupo control cuando sean utilizados para evaluar períodos de intervención de largo plazo. Abstract : Confiabilidade e responsividade do Teste da Função Manual de Jebsen‐Taylor e do Teste da Caixa e Blocos para crianças com paralisia cerebral: Objetivo: Avaliar a confiabilidade e a responsividade do Teste da Função Manual de Jebsen‐Taylor (TFMJT) e do Teste da Caixa e Blocos (TCB) para crianças com paralisia cerebral (PC). Método: Neste estudo retrospectivo, análises de confiabilidade foram realizadas com testes t pareados considerando um tempo curto (média 14d) e longo (média 120d) entre dois períodos de avaliação. Adicionalmente, coeficiente de correlacão intraclasse (CCI) foi usado para avaliar o nível de conguência. A responsividade a terapia foi conduzida com um teste t pareado em uma amostra considerando a idade, o nível de habilidade manual classificado pelo Sistema de Classificação da Habilidade Manual (MACS), e a topografia. Resultados: Nossos principais resultados confirmaram a confiabilidade dos testes em um curto período de tempo para o TFMJT em ambas as mãos e para o TCB na mão menos afetada. Estes resultados foram consistentes com o CCI. A responsividade foi confirmada, exceto na mão menos afetada para o TFMJT, com resultados similares para a abordagem por idade, MACS e topografia. Interpretação: Este estudo apóia o uso do TFMJT e do TCB para examinar mudanças após intervenções de curto prazo em crianças com PC. Estes resultados devem ser interpretados em associação com valores normativos ou um grupo controle quando usados em longos períodos de avaliação.